ROTATION AND WINDS OF EXOPLANET HD 189733 b MEASURED WITH HIGH-DISPERSION TRANSMISSION SPECTROSCOPY - Brogi, M.; Kok, R. J. de; Albrecht, S.; Snellen, I. A. G.; Birkby, J. L.; Schwarz, H. (The Astrophysical journal, 2016)
ABSTRACT Giant exoplanets orbiting very close to their parent star (hot Jupiters) are subject to tidal forces expected to synchronize their rotational and orbital periods on short timescales (tidal locking). However, spin rotation has never been measured directly for hot Jupiters. Furthermore, their atmospheres can show equatorial super-rotation via strong eastward jet streams, and/or high-altitude winds flowing from the day- to the night-side hemisphere. Planet rotation and atmospheric circulation broaden and distort the planet spectral lines to an extent that is detectable with measurements at high spectral resolution. We observed a transit of the hot Jupiter HD 189733 b around 2.3 m and at a spectral resolution of R∼105 with CRIRES at the ESO Very Large Telescope. After correcting for the stellar absorption lines and their distortion during transit (the Rossiter-McLaughlin effect), we detect the absorption of carbon monoxide and water vapor in the planet transmission spectrum by cross-correlating with model spectra. The signal is maximized (7.6 ) for a planet rotational velocity of km s−1, corresponding to a rotational period of days. This is consistent with the planet orbital period of 2.2 days, and therefore with tidal locking. We find that the rotation of HD 189733 b is longer than 1 day (3 ). The data only marginally (1.5 ) prefer models with rotation versus models without rotation. We measure a small day- to night-side wind speed of km s−1. Compared to the recent detection of sodium blueshifted by km s−1, this likely implies a strong vertical wind shear between the pressures probed by near-infrared and optical transmission spectroscopy.